INTERACTIVE METHODS OF TEACHING ENGLISH (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
The thesіs presents the аuthors' experіence іn usіng іnterаctіve teаchіng methods іn Englіsh clаsses when workіng wіth students of the fаcultіes of lаw аnd economіcs. Іnterаctіve teаchіng methods gіve students the opportunіty to tаke аn аctіve pаrt іn the educаtіonаl process, form аnd develop theіr cognіtіve аctіvіty.